2019
DOI: 10.22207/jpam.13.1.12
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Nutritional Contents of Cassava Starch Wastes Using Pleurotus ostreatus (Jacq.) P.Kumm. and Lentinus squarrosulus Mont.

Abstract: This research studied the increasing of nutritional content in cassava starch fermented with P. ostreatus (Jacq.) P.Kumm. and L. squarrosulus Mont. The cassava starch waste was supplemented with maize grain, paddy rice, rice bran, broken rice, and soybean meal at 0, 10, 20, and 30%. Solid state fermentation was carried out for 28 days. The results showed that highest reduced sugar at 86.09 g/L was found in cassava starch waste 70% + rice broken 30% fermented by L. squarrosulus Mont. The highest protein content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…However, on the contrary, previous works of Roldan-Carillo et al and Wu et al reported the amylolytic abilities of P. chrysosporium based on the detection of dextrin, maltose, and glucose (starch decomposition products) in a postculture medium [49,50]. In addition, Wirunpan et al observed the growth of P. ostreatus on a starch-containing medium, where, in comparison to the control fungus, the concentration of reducing sugar increased almost 19-fold [51].…”
Section: Screening Testmentioning
confidence: 86%
“…However, on the contrary, previous works of Roldan-Carillo et al and Wu et al reported the amylolytic abilities of P. chrysosporium based on the detection of dextrin, maltose, and glucose (starch decomposition products) in a postculture medium [49,50]. In addition, Wirunpan et al observed the growth of P. ostreatus on a starch-containing medium, where, in comparison to the control fungus, the concentration of reducing sugar increased almost 19-fold [51].…”
Section: Screening Testmentioning
confidence: 86%